Clinical patterns of speech-language disorders in thalamic aphasias - Kuljić-Obradović Dragana; Ocić Gordana G. (Vojnosanitetski Pregled)
The aim of this study was to investigate the characteristic symptom cluster and the course of aphasia in 12 patients with single left thalamic lesion verified by CAT scan. The testing of language disorder was performed by standard linguistic tests for aphasia in the acute stage and one month after the insult. Although this clinical syndrome varied greatly it was possible to point out some common characteristics. Spontaneous speech was fluent, easily articulated, grammatically correct, with preserved melodic line. Word finding and understanding were impaired. The impaired comprehension and naming were prominent in all patients with different severity. Repetition skills were intact. During the naming testing patients accomplished better results after semantic help than after phonetic help. Verbal paraphasia errors appeared more frequently (9,78) than neologistic (2,22) and literal paraphasias (1,78). Results of the language fluency tests were worse during semantic categorization tests (5,50) than during animal naming (9,89). On the basis of these facts it was presumed that aphasia in patients with dominant thalamic lesion was the result of lexico-semantic language disorder. It was statistically proved that recovery from aphasia in these cases tended to be significant and rapid.